Does owning a bank account improve reproductive and maternal health services utilization and behavior in India? Evidence from the National Family Health Survey 2015–16 - Singh, Abhishek (SSM Popul Health, 2019)
• Ownership of a bank account is associated with improved reproductive and maternal health services utilization and behaviour. • Observed associations are strongest in states where the utilization of studied services is far below the national average. • No association is found between women's ownership of a bank account and institutional delivery.